Sukces w opinii studentów Politechniki Koszalińskiej - Zychowicz, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article deals with life success circumstances. It is a report from the research conducted among Pedagogy students about their perception of life success. This article concerns changes which occurred in the thinking of the XXI century students. Research report talks about the evolution of the system of values of young people. The article presents a preliminary analysis of concept of success of the students of pedagogy of the Technical University of Koszalin. The research involved 243 people in different ages, different territorial origin, with different cultural capital. It was assumed that the collage is culture-creating factor. It have influence on choosing patterns of cultural choices by students and it promotes formation of ideas, styles and tastes. Moreover it allows to create an individual biographical scenarios.
Keywords: Politechnika Koszalińska; studenci; sukces; uczestnictwo społeczne jednostki